Pengaruh Self-Regulated Learning Terhadap Student Engagement Dalam Menghadapi E-Learning Di Masa Pandemi Covid 19 - Hafsah, Hafsah; Bismala, Lila; Firmansyah, Nunung Agus; Handayani, Susi; Siregar, Gustina; Andriany, Dewi; Hasibuan, Lailan Safina; Siregar, Hasan Sakti (Faculty of Psychology, Universitas Medan Area, 2024)
Student engagement shows how much student involvement is in learning, where this is influenced by self-regulated learning. The aim of this research is to examine the effect of self-regulated learning on student engagement. The sample in this research was 125 respondents, who were students at the Universitas Muhammadiyah Sumatera Utara, Management study program taking Production Management classes. The research results show that there is a significant influence between self-regulated learning and student engagement. Students' ability to organize their own learning has a big influence on student engagement. So it is very important to encourage self-regulated learning abilities, especially when dealing with online learning.